Design and conduct of a full diet-controlled, parallel, 2-week residential trial for diabetes prevention without weight loss in Asian Chinese and European Caucasian adults with prediabetes: the New Zealand SYNERGY study - Sequeira-Bisson, Ivana R.; Fraser, Karl; Leiu, Kok Hong; Penhaligan, Jack; Joblin-Mills, Aidan; Plank, Lindsay D.; Murphy, Rinki; Taylor, Michael W.; Gasser, Olivier; Conroy, Denise M.; Jiang, Yannan; Lu, Louise W. W.; et al. (Frontiers in Nutrition, 2025)
BackgroundThe causal underpinning of increased metabolic risk and previously observed dichotomous plasma metabolome in Asian Chinese vs. European Caucasian remains undetermined and may be hypothesised as attributed to ethnicity (genetic background), pathology (dysglycaemia) and/or lifestyle (habitual diet). We aimed to investigate the underlying cause(s) and the effect of dietary intervention on biomarkers of type 2 diabetes (T2D) in cohorts with prediabetes. The diets are a generic current Best Practice Healthy Diet (‘BPHD’), and a New Zealand-specific healthy diet (‘SYNERGY’) based on the Mediterranean Diet. We hypothesise, firstly, that 14-days of matched BPHD in Asian Chinese vs. European Caucasian cohorts (ethnicity; within-diet comparison) will attenuate the previously observed dichotomy in plasma metabolome. Secondly, that both diets will improve risk markers over 14 days vs. baseline, with significant improvement with SYNERGY compared to BPHD in Asian Chinese cohorts (diet; within-ethnicity comparison).MethodsWe conducted a 2-week, fully diet-controlled, residential trial in 20 Asian Chinese (n = 10 per diet group) and 10 European Caucasian (BPHD only) adults with prediabetes. Participants were phenotyped (dual-energy X-ray absorptiometry, magnetic resonance imaging/spectroscopy) prior to the intervention. On Day 1 (D1) and D15 assessments included anthropometry, collection of urine, faecal (microbiome analysis) and fasted blood samples, conduct of 2-h oral glucose tolerance test (established clinical, metabolome, immune markers) and indirect calorimetry (resting metabolic rate, postprandial glucose-induced thermogenesis). Additional fasted urine and blood samples were collected on D2, D7 (mid-way) and D14, with a focus group/interview on the evening of D7. Meals and snacks were calculated based on individual energy requirements for body weight maintenance, dietary compliance was supervised, and body weight monitored daily.DiscussionThis study aims to identify ethnic-specific dietary responses in a fully-controlled residential setting; to determine cause/s of the dichotomous plasma metabolome between the two ethnic groups; also to validate these biomarkers as sensitive to dietary intervention using a ‘whole of diet’ approach. Specifically, to determine the efficacy of BPHD and SYNERGY for T2D risk amelioration in the absence of body weight loss. Findings will inform design of larger ‘free-living’ community interventions and explore the feasibility of use of these diets within the community.Clinical trial registration (SPIRIT 2a)The study was prospectively registered on 22 March 2021 with the Australian New Zealand Clinical Trials Registry ACTRN12621000318886.